Audit Dosimetri pada Teknik IMRT/VMAT Terapi Radiasi pada Linear Accelarator (LINAC) - Salima, Syalima; Shabira, Nazwa Adhelia; Putri, Erlinda Ratnasari (Progressive Physics Journal, 2024)
Dosimetric audit is crucial in ensuring and improving the quality of radiation therapy, particularly in the field of radiotherapy using techniques such as Intensity-Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT). This study employs a literature review methodology, analyzing and comparing 15 articles based on dosimeters and modalities. The results indicate that various dosimetric audit methods, including the use of glass dosimeters, Gafchromic films, ion chambers, and EPID, provide accurate results in measuring doses for IMRT and VMAT techniques using LINAC. Most studies show good success rates, with dose differences between the dosimeter and the planned dose within the tolerance limits of ±5%. However, some studies also report significant dose variations, especially in organs at risk (OAR) and areas with steep dose gradients. This study highlights that routine dosimetric audits and the use of appropriate detection technologies are essential to improving the precision and safety of radiation therapy for patients.